PERAN SATUAN INTELKAM DALAM MENANGANI MARAKNYA PEREDARAN MINUMAN KERAS DI WILAYAH HUKUM POLRES CIANJUR - Erdyanthoro, Bagus (Advances in Police Science Research Journal, 2020)
ABSTRACT This research is motivated by the increasingly worrisome condition of the development of liquor distribution in Indonesia. Acts of law enforcement and rehabilitation apparently have not solved the problem so the most effective action is preventive measures. The preventive action is in the form of raising alcoholic drinks with a target focus on the people of Cianjur City because the City ranks first in the number of cases of distribution of liquor and dangerous drugs. Therefore, a study was conducted with the aim of knowing how the conditions of the role of raising liquor to the people of Cianjur City by the Cianjur SatkIntelkam Police. The study was conducted with a qualitative approach, analytical descriptive research methods, and data collection techniques through interviews, observations, and document review. The results of the study were analyzed with Management Theory, the Concept of Raising and Communication Theory concludes that the management of the implementation of liquor raising has not been going well, namely there are still shortages at each stage of the activity. Likewise with the method of raising alcohol there are deficiencies in terms of the ability of intelligence personnel. The application of the concept of raising provided by SatIntelkam is still not as expected due to the lack of understanding of SatbIntelkam personnel regarding the concept of raising itself and its implementation. Based on the results of the study, the authors suggest increasing the number and improvement of the quality of personnel with education and training, forming planning staff and developing SOPs for the implementation of liquor collection, diverting the budget allocation of contact facilities to increase the amount of intensification of raising, deepening the socialization of the concept of raising to personnel, and draw closer through the intelligence members who are in the Cianjur Police Station. In addition, it is also recommended for members of Binmas to always carry out each of the points contained in the Regulation of the Head of the Republic of Indonesia National Police Security Intelligence Agency Number 3 of 2013 concerning the Promotion of the Republic of Indonesia National Police Intelligence. Keywords: Raising, Liquor Abuse, Intelligence Unit